The twelve : a novel - Cronin, Justin (New York : Ballantine Books, 2012)
Survivors of a government-induced apocalypse endure their violent and disease-stricken world while protecting their loved ones; while a century into the future, members of a transformed society determinedly search for the original twelve virals.
Keywords: Virus diseases -- Fiction; Survival -- Fiction; End of the world -- Fiction; Human experimentation in medicine -- Fiction; Science fiction; Paranormal fiction; Fantasy fiction